Peran forda IPTTM dalam memperkenalkan kebudayaan Toraja di Kota Malang - Nida Khoirunisa; Audria Octavia Sri Anjani; Salsabillah Malicha Putri; Nanda Harda Pratama Meiji (Universitas Negeri Malang, 2021)
Regional student organizations are organizations formed through a group of students who come from one area and have the same goal. Forda IPTTM (Tongkonan Toraja Malang Youth Association) is a form of regional student organization that has the same goal among its members, namely as a communication for Toraja students who have migrated in Malang. This research focuses on how the role of Forda IPTTM in introducing Toraja culture in Malang. This study uses a qualitative approach and is described descriptively by providing a detailed description of the problem formulation in the study. In analyzing research problems, researchers used Max Weber's theory of social action and the concept of status and role. The results showed that students who have status as members and administrators have rights and obligations that must be carried out for the success of the goals of the establishment of Forda IPTTM. The role of Forda IPTTM in introducing Toraja culture is manifested through the activities and work programs they have carried out, namely participating in cultural exhibitions by presenting Toraja dances and participating in the Universitas Brawijaya Cultural Village Festival, as well as promoting Toraja culture through social media. Organisasi mahasiswa daerah ialah sebuah organisasi yang terbentuk melalui beberapa kumpulan mahasiswa yang berasal dari satu daerah dan memiliki tujuan yang sama. Forda IPTTM (Ikatan Pemuda Tongkonan Toraja Malang) merupakan salah satu bentuk organisasi mahasiswa daerah yang memiliki tujuan yang sama antar anggotanya yakni sebagai komunikasi mahasiswa Toraja yang merantau di Malang. Penelitian ini berfokus pada bagaimana peran Forda IPTTM dalam memperkenalkan kebudayaan Toraja di Malang. Peneliti menggunakan pendekatan kualitatif dan penelitian dijelaskan secara deskriptif dengan cara memberi gambaran terperinci mengenai rumusan masalah dalam penelitian. Dalam menganalisis permasalahan penelitian, teori yang digunakan peneliti adalah teori tindakan sosial Max Weber serta konsep status dan peran. Hasil penelitian menunjukkan bahwa mahasiswa yang memiliki status sebagai anggota maupun pengurus memiliki hak dan kewajiban yang harus dijalankan demi keberhasilan tujuan berdirinya Forda IPTTM. Peran Forda IPTTM dalam memperkenalkan kebudayaan Toraja diwujudkan melalui program kerja dan kegiatan yang telah mereka lakukan yakni mengikuti pameran budaya dengan menampilkan tarian Toraja dan mengikuti Festival Kampung Budaya Universitas Brawijaya, serta mempromosikan kebudayaan Toraja melalui media sosial.